A preparation method and product of a microwave dielectric tunable composite ceramic material based on barium strontium titanate with reduced dielectric constant by composite regulation

By introducing Mg2+ and Mn4+ ions into strontium titanate-based microwave dielectric ceramic materials, replacing Ti4+ at the B position in BST, the problem of excessive dielectric constant of existing lead-free microwave dielectric ceramic materials is solved, effectively reducing the dielectric constant and maintaining tunability, and is suitable for microwave communication and other fields.

CN119350018BActive Publication Date: 2025-02-28SHANDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411920545.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-02-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing lead-free microwave dielectric ceramic materials have too high dielectric constants in actual applications, resulting in signal transmission loss and delay, limiting their application in microwave communication and other fields.

Method used

By introducing Mg2+ and Mn4+ ions into strontium titanate-based microwave dielectric ceramic material, replacing Ti4+ at the B position in BST, the dielectric constant is reduced while retaining tunability.

Benefits of technology

It effectively reduces the dielectric constant of BST-based microwave dielectric ceramics from 2035 to 275, while maintaining high Q value and tunability, and is suitable for integrated and miniaturized electronic systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention discloses a preparation method and product of a strontium barium titanate-based microwave dielectric tunable composite ceramic material based on composite regulation to reduce dielectric constant. Barium strontium titanate is selected as a matrix material, and it is compounded with a low dielectric constant Mg2MnO4 dielectric material, so that the ferroelectricity of the strontium barium titanate-based composite ceramic is greatly diluted, thereby achieving an effective reduction in dielectric constant. And the tunable performance of the strontium barium titanate-based ceramic material is retained, so that it has good application prospects in the field of microwave dielectric tunability. The raw materials prepared by the present invention do not contain lead and rare earth elements, the production cost is low, and the requirements of the development of an environmentally friendly society can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of microwave dielectric tunability, and in particular to a preparation method and product of a barium strontium titanate-based microwave dielectric tunable composite ceramic material that reduces dielectric constant based on composite regulation. Background Art

[0002] The rapid development of a new generation of mobile communications based on microwave technology (such as the global positioning system (GPS), car-borne Bluetooth modules, artificial intelligence, etc.) has led to an urgent demand for microwave devices. They require the assembly of electronic systems to develop in the direction of miniaturization and integration, so the size of electronic components must be reduced. The use of microwave dielectric ceramics with high dielectric constants to replace traditional cavity resonators in microwave devices can greatly reduce the volume of the cavity. However, high dielectric constants are often accompanied by high dielectric losses. In order to meet the development of today's communication technology, microwave dielectric ceramic materials with medium dielectric constants (er<500) and high quality factors are needed. Among all microwave dielectric ceramics, tunable microwave dielectric ceramics show that the dielectric constant changes with the change of the electric field. Its biggest advantage is that its parameters such as frequency, phase or power can be adjusted as needed. This flexibility is particularly important in communication systems, radar systems and test equipment.

[0003] At present, due to the environmentally friendly development, the use of lead-based ceramics has been greatly restricted. Lead-free ABO3 perovskite structured barium strontium titanate (Ba 1-x Sr x )TiO3, abbreviated as BST) microwave dielectric tunable ceramics are considered by the industry to be one of the preferred materials to replace lead-based microwave dielectric ceramic materials due to their excellent power handling capabilities, faster response time and lower dielectric loss. However, the higher dielectric constant (1098-7200) of BST ceramic materials increases signal transmission loss and causes signal transmission delay, thus limiting practical applications.

[0004] Spinel structure oxides are key materials used as semiconductor materials and are widely used in electronic ceramics, microwave communications, photocatalysis and other fields. Among the many spinel oxide materials, manganese-containing spinel has attracted much attention because of the advantages of manganese having multiple valence states, non-toxicity, environmental protection, and low price. Studies have shown that spinels with high tetravalent manganese content are conducive to ion migration and are easily substituted with transition metal ions. The inverse spinel structure Mg2MnO4 (abbreviated as MM) has a high content of tetravalent manganese, half of which is located in the tetrahedral position, and the other half of the magnesium ions and manganese ions occupy the octahedral position together. It has a high structural symmetry, which is conducive to the migration of ions in the structure. Existing studies have shown that the transition metal ion Ti 4+ Doping into MM can improve the stability of the structure.

[0005] In short, in practical applications, microwave dielectric ceramics are expected to have a moderate dielectric constant, a high Q value and a certain degree of tunability, so as to develop lead-free microwave dielectric tunable ceramic materials that meet the requirements of microwave communications. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of existing materials and provide a method for preparing a microwave dielectric tunable composite ceramic material based on barium strontium titanate with a dielectric constant reduced by composite control. 2+ and Mn 4+ Replace Ti at the B position in BST 4+ , thereby achieving a reduction in the dielectric constant of BST-based microwave dielectric composite ceramics, and retaining the tunability of BST-based ceramics, so as to promote the development of lead-free microwave dielectric tunable ceramics. Another object of the present invention is to provide a product prepared by the above preparation method.

[0007] The purpose of the present invention is achieved through the following scheme:

[0008] The present invention provides a method for preparing a microwave dielectric tunable composite ceramic material based on barium strontium titanate for reducing dielectric constant by composite regulation. The chemical formula of the ceramic material is (1- x )Ba 0.5 Sr 0.5 TiO3- x Mg2MnO4, where 15≤ x ≤45wt%, expressed as BST50-MM; the preparation method comprises the following steps:

[0009] (1) According to the above chemical formula, BaTiO3, SrTiO3, MgO and MnO2 with a purity of not less than 99% are selected as raw materials, and the selected raw materials are dried at 80°C for 8 hours to obtain dried BaTiO3, SrTiO3, MgO and MnO2;

[0010] (2) According to the above chemical formula, weigh BaTiO3, SrTiO3, MgO and MnO2 as raw materials. 0.5 Sr 0.5 TiO3 and Mg2MnO4 are two kinds of initial powders. The two kinds of initial powders are ball-milled once using anhydrous ethanol and zirconium oxide balls of different sizes as ball-milling media, and then dried, manually ground and pre-sintered to obtain Ba 0.5 Sr 0.5 Two types of pre-sintered blocks: TiO3 and Mg2MnO4;

[0011] (3) Grinding, sieving, ball-milling and drying the two pre-burned blocks separately to obtain Ba 0.5 Sr0.5 TiO3 fine powder and Mg2MnO4 fine powder;

[0012] (4) The Ba 0.5 Sr 0.5 TiO3 fine powder and Mg2MnO4 fine powder are weighed according to mass percentage to obtain a mixed powder, wherein the amount of Mg2MnO4 fine powder is 15wt%~45wt%; the obtained mixed material is ball-milled three times and then dried to obtain a uniformly mixed mixed material;

[0013] (5) adding a polyvinyl alcohol aqueous solution with a binder concentration of 5% to the uniformly mixed mixture for granulation, wherein the amount of the binder is 10-15wt%; and obtaining small particle powder after sieving;

[0014] (6) placing the small particle powder into a mold and pressing it at 6-9 MPa to obtain a green block;

[0015] (7) After debinding the green block at 550° C., the green block is buried in zirconium oxide powder for high-temperature sintering, wherein the sintering temperature is 1380° C. and the holding time is 4 to 6 hours to obtain a BST50-MM composite ceramic;

[0016] Preferably, the first ball milling treatment in step (2) is carried out according to the ratio of initial powder: zirconium oxide balls: anhydrous ethanol = 1:2.5~4:4, and the ball milling time is 12~16 hours; the second ball milling treatment in step (3) is carried out according to the ratio of initial powder: zirconium oxide balls: anhydrous ethanol = 1:3~5:5, and the ball milling time is the same as the first ball milling time; the first ball milling treatment in step (4) is carried out according to the ratio of initial powder: zirconium oxide balls: anhydrous ethanol = 1:2.5:3, and the ball milling time is 10 hours.

[0017] Preferably, the drying temperature in steps (2), (3) and (4) is 80-120°C and the drying time is 24 hours; the pre-burning treatment temperature in step (2) is 1200-1350°C and the temperature is kept at that temperature for 4 hours.

[0018] Preferably, the tabletting pressure in step (6) is 6-9 MPa, and the pressure holding time is 0.5-1 min.

[0019] Preferably, in step (7), the debinding treatment is carried out at 550-600°C for 240-300 min, the heating rate of high temperature sintering is 3-6°C / min, the holding time is 4-6 h, and the cooling rate is 2-3°C / min.

[0020] The present invention uses the product prepared by the preparation method of the above-mentioned barium strontium titanate-based microwave dielectric tunable composite ceramic material based on composite regulation to reduce the dielectric constant. The microwave dielectric tunable composite ceramic material has a moderate dielectric constant, which satisfies the matching between impedance and high-power use very well, and is also conducive to the miniaturization and integration of devices, and has a high Q value and a certain tunability. It can achieve the purpose of effectively reducing the dielectric constant of BST-based microwave dielectric ceramics without adding other substances. Finally, the microwave dielectric tunable composite ceramic dielectric constant is achieved to be as low as 275, the Q value is as high as 256, and the tunability varies between 21.76 and 14.51%.

[0021] Beneficial Effects

[0022] The preparation method of barium strontium titanate-based microwave dielectric tunable composite ceramic material based on composite regulation to reduce the dielectric constant proposed in the present invention effectively reduces the dielectric constant of BST50 microwave dielectric tunable ceramic material from 2035 to 275, realizing the application of BST-based composite ceramic materials in the field of component preparation in integrated and miniaturized electronic systems; it proves that spinel-structured Mg2MnO4 can be used as an auxiliary material to effectively reduce the dielectric constant of perovskite structure successor materials.

[0023] In order to make the invention objectives, technical solutions and beneficial technical effects of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments.

[0024] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or each value between the endpoints of the range is included in the range. Therefore, each point or single value can be combined as its own upper limit or lower limit with any other point or single value or with other lower limits and upper limits to form an unambiguous range.

[0025] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number itself, and the “multiple” in “one or more” means two or more, and the “multiple” in “one or more” means two or more.

[0026] The above summary of the invention of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, a series of examples are used as guidance, and these embodiments can be used in various combinations. In each embodiment, the enumeration is only used as a representative group and should not be interpreted as exhaustive. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The features, advantages and technical effects of exemplary embodiments of the present application will be described below with reference to the accompanying drawings.

[0028] Figure 1 X-ray diffraction patterns of barium strontium titanate-based microwave dielectric tunable composite ceramics for reducing dielectric constants based on composite regulation according to Examples 1 to 4.

[0029] Figure 2 This is a surface microscopic morphology of the barium strontium titanate-based microwave dielectric tunable composite ceramic based on composite regulation to reduce the dielectric constant in Example 1.

[0030] Figure 3 This is a surface microscopic morphology of the barium strontium titanate-based microwave dielectric tunable composite ceramic in Example 2 that reduces the dielectric constant based on composite regulation.

[0031] Figure 4 This is a surface microscopic morphology of the barium strontium titanate-based microwave dielectric tunable composite ceramic in Example 3 that reduces the dielectric constant based on composite regulation.

[0032] Figure 5 This is a surface microscopic morphology of the barium strontium titanate-based microwave dielectric tunable composite ceramic of Example 4 that reduces the dielectric constant based on composite regulation. DETAILED DESCRIPTION

[0033] Example

[0034] The following examples may more specifically describe the disclosure of the present invention, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of this application will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight ratios, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0035] Example 1

[0036] The barium strontium titanate-based microwave dielectric tunable composite ceramic material for reducing dielectric constant by composite regulation described in this embodiment comprises the following components based on the total weight of the raw materials:

[0037] Matrix material BST50 85wt%

[0038] Dielectric material MM 15wt%

[0039] The method for preparing the barium strontium titanate-based microwave dielectric tunable composite ceramic material based on composite regulation to reduce the dielectric constant described in this embodiment comprises the following steps:

[0040] (1) According to the above chemical formula, BaTiO3, SrTiO3, MgO and MnO2 with a purity of not less than 99% are selected as raw materials, and the selected raw materials are dried at 80°C for 8 hours to obtain dried BaTiO3, SrTiO3, MgO and MnO2;

[0041] (2) Using the dried BaTiO3, SrTiO3 and MgO, MnO2 as raw materials, two initial powders of Ba0.5Sr0.5TiO3 and Mg2MnO4 were weighed respectively, and the two initial powders were ball-milled using anhydrous ethanol and zirconium oxide balls of different sizes as ball-milling media, with the ratio of initial powder: zirconium ball: anhydrous ethanol being 1:3:4, and the ball-milling time being 12 hours, followed by drying at 80°C for 24 hours, and then manually grinding and pre-calcining to obtain Ba 0.5 Sr 0.5 TiO3 and Mg2MnO4 are two kinds of pre-sintered blocks, of which Ba 0.5 Sr 0.5 The pre-sintering temperature of TiO3 is 1250℃, the pre-sintering temperature of Mg2MnO4 is 1200℃, and the holding time is 4 hours;

[0042] (3) The two pre-sintered blocks were ground, sieved, and ball-milled for a second time, with the ratio of material: zirconium ball: anhydrous ethanol = 1:3:5, and the ball-milling time was 16 hours, and then dried at 80°C to obtain Ba 0.5 Sr 0.5 TiO3 fine powder and Mg2MnO4 fine powder;

[0043] (4) The Ba 0.5 Sr 0.5 TiO3 fine powder and Mg2MnO4 fine powder are weighed according to mass percentage to obtain a mixed powder, wherein the amount of Mg2MnO4 fine powder is 15wt%; the obtained mixed material is ball-milled three times, the material during ball milling: zirconium ball: anhydrous ethanol = 1:2:3, the ball milling time is 10 hours, and then dried to obtain a uniformly mixed mixed material;

[0044] (5) adding a polyvinyl alcohol aqueous solution with a binder concentration of 5% to the uniformly mixed mixture for granulation, wherein the amount of the binder is 12wt%; and obtaining small particle powder after sieving;

[0045] (6) placing the small particle powder into a mold and pressing it at 7 MPa to obtain a green block;

[0046] (7) The green block is subjected to a binder removal treatment at 550°C, and the binder removal holding time is 4 hours. The debinded block is then buried in zirconium oxide powder for high-temperature sintering treatment, wherein the sintering temperature is 1380°C, the holding time is 6 hours, the heating rate is 3°C / h, and the cooling rate is 2°C / h, to obtain Ba 0.5 Sr 0.5 TiO3-Mg2MnO4 composite ceramics.

[0047] The XRD spectrum of the barium strontium titanate-based microwave dielectric tunable composite ceramic based on composite regulation to reduce the dielectric constant described in this embodiment is as follows Figure 1 As shown, it can be seen that only Ba 0.5 Sr 0.5 The two phases of TiO3 and Mg2MnO4 have no impurities, which indicates that the two phases will not undergo chemical reactions and can exist independently; the surface morphology SEM image of the microwave dielectric tunable composite ceramic based on strontium barium titanate to reduce the dielectric constant based on composite regulation described in this embodiment is as follows Figure 2 As shown, it can be clearly seen that there are two types of grains, the ceramic sample has fewer pores and higher density; the dielectric constant of the microwave dielectric tunable composite ceramic is 927, the Q value is 256, and the tunability under a bias electric field of 20 kV / cm is 22.17%.

[0048] Example 2

[0049] The barium strontium titanate-based microwave dielectric tunable composite ceramic material for reducing dielectric constant by composite regulation described in this embodiment comprises the following components based on the total weight of the raw materials:

[0050] Matrix material BST50 75wt%

[0051] Dielectric material MM 25wt%

[0052] The method for preparing the barium strontium titanate-based microwave dielectric tunable composite ceramic material based on composite regulation to reduce the dielectric constant described in this embodiment comprises the following steps:

[0053] (1) According to the above chemical formula, BaTiO3, SrTiO3, MgO and MnO2 with a purity of not less than 99% are selected as raw materials, and the selected raw materials are dried at 80°C for 8 hours to obtain dried BaTiO3, SrTiO3, MgO and MnO2;

[0054] (2) Take the dried BaTiO3, SrTiO3, MgO and MnO2 as raw materials and weigh Ba 0.5 Sr 0.5TiO3 and Mg2MnO4 are two initial powders. The two initial powders are respectively subjected to a ball milling treatment using anhydrous ethanol and zirconium oxide balls of different sizes as ball milling media. The initial powder: zirconium ball: anhydrous ethanol = 1:3:4. The ball milling time is 12 hours. Then, the powder is dried at 80°C for 24 hours. After manual grinding and pre-sintering, Ba 0.5 Sr 0.5 TiO3 and Mg2MnO4 are two kinds of pre-sintered blocks, of which Ba 0.5 Sr 0.5 The pre-sintering temperature of TiO3 is 1250℃, the pre-sintering temperature of Mg2MnO4 is 1200℃, and the holding time is 4 hours;

[0055] (3) The two pre-sintered blocks were ground, sieved, and ball-milled for a second time, with the ratio of material: zirconium ball: anhydrous ethanol = 1:3:5, and the ball-milling time was 16 hours, and then dried at 80°C to obtain Ba 0.5 Sr 0.5 TiO3 fine powder and Mg2MnO4 fine powder;

[0056] (4) The Ba 0.5 Sr 0.5 TiO3 fine powder and Mg2MnO4 fine powder are weighed according to mass percentage to obtain a mixed powder, wherein the amount of Mg2MnO4 fine powder is 25wt%; the obtained mixed material is ball-milled three times, the material during ball milling: zirconium ball: anhydrous ethanol = 1:2:3, the ball milling time is 10 hours, and then dried to obtain a uniformly mixed mixed material;

[0057] (5) Adding a polyvinyl alcohol aqueous solution with a binder concentration of 5% to the uniformly mixed mixture for granulation, wherein the amount of the binder is 12wt%; and obtaining small particle powder after sieving;.

[0058] (6) placing the small particle powder into a mold and pressing it at 7 MPa to obtain a green block;

[0059] (7) The green block is subjected to a binder removal treatment at 550°C, and the binder removal holding time is 4 hours. The debinded block is then buried in zirconium oxide powder for high-temperature sintering treatment, wherein the sintering temperature is 1380°C, the holding time is 6 hours, the heating rate is 3°C / h, and the cooling rate is 2°C / h, to obtain Ba 0.5 Sr 0.5 TiO3-Mg2MnO4 composite ceramics.

[0060] The XRD spectrum of the barium strontium titanate-based microwave dielectric tunable composite ceramic based on composite regulation to reduce the dielectric constant described in this embodiment is as follows Figure 1 As shown, it can be seen that only Ba0.5 Sr 0.5 The two phases of TiO3 and Mg2MnO4 have no impurities, which indicates that the two phases will not undergo chemical reactions and can exist independently; the surface morphology SEM image of the microwave dielectric tunable composite ceramic based on strontium barium titanate to reduce the dielectric constant based on composite regulation described in this embodiment is as follows Figure 3 As shown, it can be clearly seen that there are two types of grains, the blocky grains are increased, and the density is higher; the dielectric constant of the microwave dielectric tunable composite ceramic is 716, the Q value is 194, and the tunability under a bias electric field of 20 kV / cm is 18.12%.

[0061] Example 3

[0062] The barium strontium titanate-based microwave dielectric tunable composite ceramic material for reducing dielectric constant by composite regulation described in this embodiment comprises the following components based on the total weight of the raw materials:

[0063] Matrix material BST50 65wt%

[0064] Dielectric material MM 35wt%

[0065] The method for preparing the barium strontium titanate-based microwave dielectric tunable composite ceramic material based on composite regulation to reduce the dielectric constant described in this embodiment comprises the following steps:

[0066] (1) According to the above chemical formula, BaTiO3, SrTiO3, MgO and MnO2 with a purity of not less than 99% are selected as raw materials, and the selected raw materials are dried at 80°C for 8 hours to obtain dried BaTiO3, SrTiO3, MgO and MnO2;

[0067] (2) Using the dried BaTiO3, SrTiO3 and MgO, MnO2 as raw materials, two initial powders of Ba0.5Sr0.5TiO3 and Mg2MnO4 were weighed respectively, and the two initial powders were ball-milled using anhydrous ethanol and zirconium oxide balls of different sizes as ball-milling media, with the ratio of initial powder: zirconium ball: anhydrous ethanol being 1:3:4, and the ball-milling time being 12 hours, followed by drying at 80°C for 24 hours, and then manually grinding and pre-calcining to obtain Ba 0.5 Sr 0.5 TiO3 and Mg2MnO4 are two kinds of pre-sintered blocks, of which Ba 0.5 Sr 0.5 The pre-sintering temperature of TiO3 is 1250℃, the pre-sintering temperature of Mg2MnO4 is 1200℃, and the holding time is 4 hours;

[0068] (3) The two pre-sintered blocks were ground, sieved, and ball-milled for a second time, with the ratio of material: zirconium ball: anhydrous ethanol = 1:3:5, and the ball-milling time was 16 hours, and then dried at 80°C to obtain Ba 0.5 Sr 0.5 TiO3 fine powder and Mg2MnO4 fine powder;

[0069] (4) The Ba 0.5 Sr 0.5 TiO3 fine powder and Mg2MnO4 fine powder are weighed according to mass percentage to obtain a mixed powder, wherein the amount of Mg2MnO4 fine powder is 35wt%; the obtained mixed material is ball-milled three times, the material during ball milling: zirconium ball: anhydrous ethanol = 1:2:3, the ball milling time is 10 hours, and then dried to obtain a uniformly mixed mixed material;

[0070] (5) adding a polyvinyl alcohol aqueous solution with a binder concentration of 5% to the uniformly mixed mixture for granulation, wherein the amount of the binder is 12wt%; and obtaining small particle powder after sieving;

[0071] (6) placing the small particle powder into a mold and pressing it at 7 MPa to obtain a green block;

[0072] (7) The green block is subjected to a binder removal treatment at 550°C, and the binder removal holding time is 4 hours. The debinded block is then buried in zirconium oxide powder for high-temperature sintering treatment, wherein the sintering temperature is 1380°C, the holding time is 6 hours, the heating rate is 3°C / h, and the cooling rate is 2°C / h, to obtain Ba 0.5 Sr 0.5 TiO3-Mg2MnO4 composite ceramics.

[0073] The XRD spectrum of the barium strontium titanate-based microwave dielectric tunable composite ceramic based on composite regulation to reduce the dielectric constant described in this embodiment is as follows Figure 1 As shown, it can be seen that only Ba 0.5 Sr 0.5 The two phases of TiO3 and Mg2MnO4 have no impurities, which indicates that the two phases will not undergo chemical reactions and can exist independently; the surface morphology SEM image of the microwave dielectric tunable composite ceramic based on strontium barium titanate to reduce the dielectric constant based on composite regulation described in this embodiment is as follows Figure 4 As shown, it can be clearly seen that there are two types of grains, the blocky grains are increased, the blocky grains are inlaid with the granular grains, and the density is high; the dielectric constant of the microwave dielectric tunable composite ceramic is 486, the Q value is 136, and the tunability under a bias electric field of 20 kV / cm is 15.43%.

[0074] Example 4

[0075] The barium strontium titanate-based microwave dielectric tunable composite ceramic material for reducing dielectric constant by composite regulation described in this embodiment comprises the following components based on the total weight of the raw materials:

[0076] Matrix material BST50 55wt%

[0077] Dielectric material MM 45wt%

[0078] The method for preparing the barium strontium titanate-based microwave dielectric tunable composite ceramic material based on composite regulation to reduce the dielectric constant described in this embodiment comprises the following steps:

[0079] (1) According to the above chemical formula, BaTiO3, SrTiO3, MgO and MnO2 with a purity of not less than 99% are selected as raw materials, and the selected raw materials are dried at 80°C for 8 hours to obtain dried BaTiO3, SrTiO3, MgO and MnO2;

[0080] (2) Take the dried BaTiO3, SrTiO3, MgO and MnO2 as raw materials and weigh Ba 0.5 Sr 0.5 TiO3 and Mg2MnO4 are two initial powders. The two initial powders are respectively subjected to a ball milling treatment using anhydrous ethanol and zirconium oxide balls of different sizes as ball milling media. The initial powder: zirconium ball: anhydrous ethanol = 1:3:4. The ball milling time is 12 hours. Then, the powder is dried at 80°C for 24 hours. After manual grinding and pre-sintering, Ba 0.5 Sr 0.5 TiO3 and Mg2MnO4 are two kinds of pre-sintered blocks, of which Ba 0.5 Sr 0.5 The pre-sintering temperature of TiO3 is 1250℃, the pre-sintering temperature of Mg2MnO4 is 1200℃, and the holding time is 4 hours;

[0081] (3) The two pre-sintered blocks were ground, sieved, and ball-milled for a second time, with the ratio of material: zirconium ball: anhydrous ethanol = 1:3:5, and the ball-milling time was 16 hours, and then dried at 80°C to obtain Ba 0.5 Sr 0.5 TiO3 fine powder and Mg2MnO4 fine powder;

[0082] (4) The Ba 0.5 Sr 0.5TiO3 fine powder and Mg2MnO4 fine powder are weighed according to mass percentage to obtain a mixed powder, wherein the amount of Mg2MnO4 fine powder is 45wt%; the obtained mixed material is ball-milled three times, the material during ball milling: zirconium ball: anhydrous ethanol = 1:2:3, the ball milling time is 10 hours, and then dried to obtain a uniformly mixed mixed material;

[0083] (5) adding a polyvinyl alcohol aqueous solution with a binder concentration of 5% to the uniformly mixed mixture for granulation, wherein the amount of the binder is 12wt%; and obtaining small particle powder after sieving;

[0084] (6) placing the small particle powder into a mold and pressing it at 7 MPa to obtain a green block;

[0085] (7) The green block is subjected to a binder removal treatment at 550°C, and the binder removal holding time is 4 hours. The debinded block is then buried in zirconium oxide powder for high-temperature sintering treatment, wherein the sintering temperature is 1380°C, the holding time is 6 hours, the heating rate is 3°C / h, and the cooling rate is 2°C / h, to obtain Ba 0.5 Sr 0.5 TiO3-Mg2MnO4 composite ceramics.

[0086] The XRD spectrum of the barium strontium titanate-based microwave dielectric tunable composite ceramic based on composite regulation to reduce the dielectric constant described in this embodiment is as follows Figure 1 As shown, it can be seen that only Ba 0.5 Sr 0.5 The two phases of TiO3 and Mg2MnO4 have no impurities, which indicates that the two phases will not undergo chemical reactions and can exist independently; the surface morphology SEM image of the microwave dielectric tunable composite ceramic based on strontium barium titanate to reduce the dielectric constant based on composite regulation described in this embodiment is as follows Figure 5 As shown, it can be clearly seen that there are two types of grains, most of which are blocky grains. The ceramic sample has more pores and general density. The dielectric constant of the microwave dielectric tunable composite ceramic is 275, the Q value is 113, and the tunability under a bias electric field of 20 kV / cm is 14.51%.

[0087] The above is only a specific implementation of the present application, but the implementation scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A method for preparing a microwave dielectric tunable composite ceramic material based on barium strontium titanate with reduced dielectric constant based on composite regulation, characterized in that: The chemical formula of the microwave dielectric tunable composite ceramic material is (1- x )Ba 0.5 Sr 0.5 TiO3- x Mg2MnO4, where 15≤ x ≤45wt%, expressed as BST50-MM; the preparation method of the microwave dielectric tunable composite ceramic material comprises the following steps: (1) According to the above chemical formula, BaTiO3, SrTiO3, MgO and MnO2 with a purity of not less than 99% are selected as raw materials, and the selected raw materials are dried at 80°C for 8 hours to obtain dried BaTiO3, SrTiO3, MgO and MnO2; (2) According to the above chemical formula, weigh BaTiO3, SrTiO3, MgO and MnO2 as raw materials. 0.5 Sr 0.5 TiO3 and Mg2MnO4 are two kinds of initial powders. The two kinds of initial powders are ball-milled once using anhydrous ethanol and zirconium oxide balls of different sizes as ball-milling media, and then dried, manually ground and pre-sintered to obtain Ba 0.5 Sr 0.5 Two types of pre-sintered blocks: TiO3 and Mg2MnO4; (3) Grinding, sieving, ball-milling and drying the two pre-burned blocks separately to obtain Ba 0.5 Sr 0.5 TiO3 fine powder and Mg2MnO4 fine powder; (4) The Ba 0.5 Sr 0.5 TiO3 fine powder and Mg2MnO4 fine powder are weighed according to mass percentage to obtain a mixed powder, wherein the amount of Mg2MnO4 fine powder is 15wt%~45wt%; the obtained mixed material is ball-milled three times and then dried to obtain a uniformly mixed mixed material; (5) adding a polyvinyl alcohol aqueous solution with a binder concentration of 5% to the uniformly mixed mixture for granulation, wherein the amount of the binder is 10-15wt%; and obtaining small particle powder after sieving; (6) placing the small particle powder into a mold, and pressing and molding the green block at 6-9 MPa, with the holding time being 0.5-1 min; (7) After the green block is subjected to a binder removal treatment, it is buried in zirconium oxide powder and subjected to a high-temperature sintering treatment, wherein the sintering temperature is 1380° C. and the holding time is 4 to 6 hours to obtain Ba 0.5 Sr 0.5 TiO3-Mg2MnO4 composite ceramics.

2. The method for preparing a microwave dielectric tunable composite ceramic material based on barium strontium titanate with reduced dielectric constant based on composite regulation according to claim 1, characterized in that: The first ball milling treatment in step (2) is carried out under the condition that the ratio of initial powder: zirconium oxide balls: anhydrous ethanol is 1:2.5-4:4, and the ball milling time is 12-16 hours; the second ball milling treatment in step (3) is carried out under the condition that the ratio of initial powder: zirconium oxide balls: anhydrous ethanol is 1:3-5:5, and the ball milling time is the same as the first ball milling time; the third ball milling treatment in step (4) is carried out under the condition that the ratio of initial powder: zirconium oxide balls: anhydrous ethanol is 1:2.5:3, and the ball milling time is 10 hours.

3. The method for preparing a microwave dielectric tunable composite ceramic material based on barium strontium titanate with reduced dielectric constant based on composite regulation according to claim 1, characterized in that: In the steps (2), (3) and (4), the drying temperature is 80-120°C and the drying time is 24 hours; in the step (2), the pre-burning temperature is 1200-1350°C and the temperature is kept for 4 hours.

4. The method for preparing a microwave dielectric tunable composite ceramic material based on barium strontium titanate with reduced dielectric constant based on composite regulation according to claim 1, characterized in that: In step (7), the debinding treatment is carried out at 550-600°C for 240-300 min, the heating rate of the high temperature sintering is 3-6°C / min, and the cooling rate is 2-3°C / min.

5. A product obtained by using the method for preparing barium strontium titanate-based microwave dielectric tunable composite ceramic material based on composite regulation to reduce dielectric constant as described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Microwave dielectrically-adjustable material of barium strontium titanate composite molybdate and preparation method for same

    CN102515746A

  • Non-stoichiometric barium-strontium-titanate-based dielectric ceramic material and preparation method

    CN105218088A